Effectiveness of Academic Engagement Training on the Ability to Forgiveness and increasing Positive Orientation Towards School - Vajiheh Zohoorparvandeh; Elham Zirak (مطالعات روانشناسی تربیتی)
The present study was conducted with the aim of investigating the effectiveness of academic engagement training on the ability to forgiveness and increasing Positive Orientation Towards School. The research method was applied in terms of objective and semi-experimental research design with a pre-test-post-test design with a control group. The statistical population of the research included female students of the second secondary school in Mashhad in the academic year of 2021-2022. In this research, 30 students were selected by multi-stage cluster sampling method and randomly assigned to experimental and control groups (15 students in the experimental group and 15 students in the control group). The experimental group received academic engagement training intervention during two months in 12 75-minute sessions. The questionnaires used in this research included Ehteshamzadeh et al.'s forgiveness (2009), positive orientation towards School Ahmadi & etal (2016). The data obtained from the research were analyzed by covariance analysis using SPSS software version 23. The results showed that teaching academic engagement has a significant effect on the ability to forgiveness and increasing Positive Orientation Towards School. In this way, this intervention was able to increase the ability of forgiveness and positive orientation of high school students; Therefore, it can be said that teaching academic engagement by using techniques such as familiarity with the concept of forgiveness, accepting emotions, facing emotions, individual and collective responsibility skills, and self-awareness can be an effective method to increase the ability to forgive and have a positive orientation towards school in knowledge. Secondary